The Soviet and Russian Navies. From the Cold War to the Cold war 2.0, 1945 - 2024 - Muraviev, Alexey (Taylor & Francis, 2025)
This handbook brings together historical and contemporary essays about Soviet and Russian military studies, to offer a comprehensive volume on the topic.